The Faktor Penentu Kinerja Pegawai Pemerintah: Peran Motivasi Kerja, Locus of Control, dan Kompensasi melalui Kepuasan Kerja: This study aims to analyze the influence of work motivation, locus of control, and compensation on employee performance through job satisfaction as an intervening variable at the Inspectorate of the East Java Provincial Government - Wanda Gema Hidayat; RAJESH PRETTYPAL SINGH (ULTIMA Management, 2026)
This study aims to analyze the influence of work motivation, locus of control, and compensation on employee performance through job satisfaction as an intervening variable at the Inspectorate of the East Java Provincial Government. The research employed a quantitative approach using a census sampling technique involving 120 employees and staff members of the organization. Data were collected through questionnaires and interviews and analyzed using Structural Equation Modeling (SEM) with IBM SPSS AMOS 23.0. The findings indicate that work motivation, locus of control, and compensation have a significant positive effect on job satisfaction. In addition, job satisfaction has a significant positive effect on employee performance. The results also reveal that work motivation, locus of control, and compensation directly and significantly influence employee performance. Furthermore, job satisfaction is proven to mediate the relationship between work motivation, locus of control, and compensation on employee performance. These findings suggest that improving employee motivation, strengthening employees’ internal locus of control, and providing appropriate compensation can enhance job satisfaction and ultimately improve employee performance within government institution. This study contributes to the public sector human resource management literature by addressing the limited empirical evidence on the mediating role of job satisfaction in the relationship between work motivation, locus of control, compensation, and employee performance within a government inspectorate institution.